Spectrophotometric evaluation of calcium ion release from different calcium hydroxide preparations: An in-vitro study. - Atul Jain; Kanchan Bhadoria; Hemendra Singh Hada (Universidad de Concepción., 2017)
Pulp tissue conditions such as infections have long been treated with calcium hydroxide (CaOH). In the last decade, use of mineral trioxide aggregate (MTA) has gained ground. This study was carried out to comparatively evaluate the Ca release from CaOH powder with different vehicles and different types of MTA. Materials and Methods: 40 single rooted mandibular premolars were selected, decoronated and biomechanically prepared. They were randomly divided into four groups, consisting of 10 samples each. Root canals were packed with different preparations of CaOH and MTA. Calcium ion release was evaluated with an UV-spectrophotometer. Result: Amongst the CaOH preparations, using propylene glycol as a vehicle produced extended release of calcium ions (7.34±0.01) for a period of 14 days. Whereas, amongst MTA based products, MTA angelus produced the maximum release of calcium ions (2.42±0.010). A statistically significant difference was present between the four groups (p<0.05). Conclusion: Propylene glycol mixed with CaOH powder, produces a higher and extended release of calcium ions compared to distilled water. MTA angelus produces consistent calcium ion release.